MdSWEET23, a sucrose transporter from apple (Malus × domestica Borkh.), influences sugar metabolism and enhances cold tolerance in tomato - Nie, Peixian; Wang, Laiping; Li, Miao; Lyu, Deguo; Qin, Sijun; Xue, Xiaomin (Frontiers in Plant Science, 2023)
Photosynthetic products in most fleshy fruits are unloaded via the apoplasmic pathway.Sugar transporters play an important role in the apoplasmic unloading pathway and are involved in sugar transport for fruit development. The MdSWEET23, cloned from ''Hanfu'' apple (Malus × domestica Borkh.) fruits, belongs to Clade III of the SWEET family. Subcellular localization revealed that MdSWEET23 is localized on the plasma membrane. β-glucuronidase activity assays showed that MdSWEET23 was primarily expressed in the sepal and carpel vascular bundle of apple fruits.Heterologous expression assays in yeast showed that MdSWEET23 functions in sucrose transport.The overexpression of MdSWEET23 in the ''Orin" calli increased the soluble sugar content. The silencing of MdSWEET23 significantly reduced the contents of sucrose and sorbitol in apple fruits.Ectopic overexpression of MdSWEET23 in tomato altered sugar metabolism and distribution in leaves and fruits, causing a reduction in photosynthetic rates and plant height, and increased the content of sucrose, fructose, and glucose in breaking color fruits, but did not increase sugar sink potency of tomato fruits.